A CONCEPTUAL MODEL COMBINATION FOR THE UNIFICATION OF DESIGN AND TOLERANCING IN ROBUST DESIGN. (May 2020) - Grauberger, P.; Goetz, S.; Schleich, B.; Gwosch, T.; Matthiesen, S.; Wartzack, S.
Abstract: In design engineering, the early consideration of tolerance chains contributes to robust design. For this, a link of design and tolerancing domains is essential. This paper presents a combination of the graph-based tolerancing approach and the Contact and Channel approach to link these domains. The combined approach is applied at a coinage machine. Here it provides detailed insights into state-dependent relations of embodiment and functions, which can improve robustness evaluation of the concept. This approach shows a possibility to bridge the gap between design and tolerancing domains.